First evaluation of the microbiome of built cultural heritage by using the Ion Torrent next generation sequencing platform. (July 2018) - Adamiak, Justyna; Otlewska, Anna; Tafer, Hakim; Lopandic, Ksenija; Gutarowska, Beata; Sterflinger, Katja; Piñar, Guadalupe
Abstract: The aim of this study was to detect the community structure of Bacteria and Archaea, especially halophilic microorganisms, involved in the biodeterioration of historic building materials, as brick and paint coating. The Ion Torrent™ sequencing technology platform was used for the first time to analyse these materials. Amplicons were generated by using universal, bacteria- and archaea-specific primers, all flanking the V4 hypervariable region of the 16S rDNA, in order to compare the sensitivity of taxon detection. Results showed that the Ion Torrent™ sequencing platform has an enormous potential to evaluate the microbiome of historic building materials in a fast and easy way. The brick sample displayed a total of 1178 genera belonging to 27 bacterial and 3 archaeal phyla, while the paint coating showed 145 genera belonging to 11 bacterial phyla. Members of the Actinobacteria were dominant in both samples. Halophiles were detected in both materials showing to be important colonizers when salty micro-niches are available in the surfaces of the buildings. Nevertheless, analyses showed to be influenced by the primer choice, and bacteria- and archaea-specific primers confirmed the occurrence of primer bias, as they enabled the unspecific detection of Archaea and Bacteria. The results derived from universal and archaeal-specific primers were comparable, except for Nitrospirae, detected only using universal primers. These data clearly showed the impact of primer choice on the structure of the microbial communities, pointing out the need of a carefully choice of primers. Therefore, we recommend using, in addition to the universal primers, bacteria- and archaea-specific primers in order to cover a higher taxonomic diversity. Highlights: Ion Torrent sequencing technology was used to analyse historic building materials. Ion Torrent sequencing has potential to evaluate the microbiome of historic materials. Halophiles are important colonizers when salty niches are available in the buildings. Primer choice has significant impact on the structure of the microbial communities.